2021
DOI: 10.1038/s41598-021-94138-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of malnutrition on severity of COVID-19

Abstract: The COVID-19 pandemic is a public health crisis that has the potential to exacerbate worldwide malnutrition. This study examines whether patients with a history of malnutrition are predisposed to severe COVID-19. To do so, data on 103,099 COVID-19 inpatient encounters from 56 hospitals in the United States between March 2020 and June 2020 were retrieved from the Cerner COVID-19 Dataset. Patients with a history of malnutrition between 2015 and 2019 were identified, and a random intercept logistic regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 33 publications
2
54
1
Order By: Relevance
“…However, it is not excluded that malnutrition may precede the infection. A recent study showed that patients with a recent history of malnutrition could be at higher risk of severe COVID-19 [34]. The majority of our patients had comorbidities that could lead to malnutrition.…”
Section: Discussionmentioning
confidence: 77%
“…However, it is not excluded that malnutrition may precede the infection. A recent study showed that patients with a recent history of malnutrition could be at higher risk of severe COVID-19 [34]. The majority of our patients had comorbidities that could lead to malnutrition.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, malnutrition is linked to higher serum HA levels [ 96 ]. Furthermore, the long‑term effects of malnutrition predispose patients to severe COVID‑19 in an age‑dependent manner [ 97 ], and are associated with hyperinflammation and immunosuppression [ 98 ]. How malnutrition affects glutamine levels remains to be determined.…”
Section: Consequences Of Glutamine Deficiency and Covid-19mentioning
confidence: 99%
“… 32 On the other hand, as children age, the risk posed by a history of malnutrition to children with severe COVID-19 decreases only slightly and is highest in younger children (under 5 years of age). 29 At the same time, the length of hospital stay was significantly prolonged in children with other viral (such as adenovirus, rhinovirus, enterovirus, etc.) infections.…”
Section: Epidemiological Characteristics Of Covid-19 In Childrenmentioning
confidence: 99%